Effect of fruit size and coating material on quality of tangerine fruit cv. Sai Nam Phueng - Boonyakiat D. (Chiang Mai University, 2015)
Small (No. 4; 92-98 g) and large (No. 6; 134-142 g) tangerine fruit coated with either Zivdar or Fomesa as well as a non-coated control were stored at room temperature (24±3°C) and 59±6% relative humidity for 10 days. The results showed that large fruit had lower weight loss, less off-flavor and better visual appearance than small fruit. Fruit size also had an effect on hue angle of peel color, pH, total soluble solids (TSS) and titratable acidity (TA) but had no effect on internal O2, internal CO2, ethanol content in juice, pyruvate decarboxylase (PDC) and alcohol dehydrogenase (ADH) activity, L* and chroma of peel color, TSS/TA ratio and vitamin C content. Tangerine fruit coated with Fomesa had the lowest weight loss. Fruit coated with Zivdar had higher O2 and CO2 exchange and lower internal ethanol in fruit juice than fruit coated with Fomesa. The coating affected the flavor and visual appearance quality of tangerine fruit, but had no effect on enzyme activities, peel color and chemical composition.